PERANAN AKUNTANSI DALAM AKUNTABILITAS DANA DESA DAN UMKM DI DESA AIR DUREN KECAMATAN PEMALI KABUPATEN BANGKA - Abu Nizarudin (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
This KKN activity aims to provide accounting assistance for village finances, assist villages in preparing Village Financial Reports, and provide an understanding of the importance of bookkeeping or accounting for UMKM.This KKN was carried out in Air Duren Village, Pemali Subdistrict, Bangka Regency with 40 students from various study programs at the Universitas Bangka Belitung from July 27 to September 2, 2015.The KKN work programs are: 1) Debriefing to students from the BPKP Expert Team of Bangka Belitung Representative and Supervisors, 2) Socializing the Village Law from the BPKP Expert Team, KKN Students and KKN Field Supervisors at the Universitas Bangka Belitung, 3) Socializing the importance of bookkeeping for UMKM, 4) Assistance in preparing Village Accounting and Finance, and assistance in preparing Village Financial Reports.The result of this KKN activity is that students are able to transfer knowledge through their work program in accordance with their respective fields of knowledge to assist the preparation of Village Financial Reports, so that the perpetrators can understand the importance of accounting. Furthermore, it is recommended that accounting training be routinely held for village officials and UMKM actors.